THE EFFECT OF USING FLY SWATTER GAME AS THE MEDIA IN TEACHING VOCABULARY AT SEVENTH GRADE OF MTS AL-WASHLIYAH MEDAN - Nurmila Cahyani Harahap, Zulfitri (PUSKAPAD, 2022)
The research aimed to find out the effect of using fly swatter game as the media in teaching vocabulary. This research was conducted by using experimental method. The experimental method designed were used two classes which were taught two different media. The experiment class was taught with media fly swatter game, and the control class was taught without media fly swatter game. The subject of this research was grade VII of MTs Al-Washliyah Medan Academic Year 2021/2022. The population of students consisted of 160 students; the sample was 50 students (25 students’ experimental class and 25 students’ control class). This research was conducted through the following procedures : giving pre-test, applying treatments, and giving post-test. The test is multiple choices and essay, which consist of 20 items to both of experimental group and control group in pre-test and post-test. The data was analyzed by using T-test formula. The result of the research there was a difference score between students’ score in learning vocabulary by using fly swatter game and without fly swatter game. The mean score of control class, pre-test got 37 and post-test got 56,2 and for the mean score of experimental class, pre-test got 50,8 and post-test got 79,2. The result that found in this research t observed was 15.578 and t table 2.0106. In conclusion, fly swatter game effectively be used to teach vocabulary learning of seven grade students of MTs. Al-Washliyah Medan.